1986
DOI: 10.2337/diab.35.3.329
|View full text |Cite
|
Sign up to set email alerts
|

Cold Exposure Reverses the Diabetogenic Effects of High-Fat Feeding

Abstract: Long-term cafeteria feeding, cold exposure, and the combination of treatments increased energy intake in female Wistar rats by 25%, 113%, and 150%, respectively, in comparison with controls (P less than 0.01). Although cafeteria feeding at room temperature markedly increased the insulin response to an intravenous glucose tolerance test (IVGTT), glucose tolerance was deteriorated (P less than 0.01). In contrast, cold exposure significantly improved glucose tolerance in the presence of a reduced insulin response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
25
0
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 9 publications
8
25
0
1
Order By: Relevance
“…demonstrated that cold exposure improved the glucose clearance of rodents during a glucose tolerance test. 19 In agreement with the previous findings, control mice showed markedly improved glucose tolerance after cold exposure (Figure 2f). In mice expressing HOXC10, glucose disposal was less efficient compared with control mice (Figure 2f).…”
Section: Hoxc10 Suppresses Browning Of Subq Wat In Vivosupporting
confidence: 81%
“…demonstrated that cold exposure improved the glucose clearance of rodents during a glucose tolerance test. 19 In agreement with the previous findings, control mice showed markedly improved glucose tolerance after cold exposure (Figure 2f). In mice expressing HOXC10, glucose disposal was less efficient compared with control mice (Figure 2f).…”
Section: Hoxc10 Suppresses Browning Of Subq Wat In Vivosupporting
confidence: 81%
“…In this experiment with congenic mice (Table 4), there was no significant hyperglycemia detected in the wild-type mice, even though it is well established that B6 mice develop diabetes when fed this high-fat diet (20). Since this high-fat feeding experiment was conducted at reduced temperature, the increased energy expenditure to maintain body temperature probably reduced hyperglycemia, as previously described for rats fed a high-fat diet (21).…”
Section: Figurementioning
confidence: 74%
“…Mice Activated BAT protects against diet-induced obesity (Cawthorne et al, 1984;Peirce and Vidal-Puig, 2013;Vallerand et al, 1986). We, therefore, hypothesized that Apom À/À mice would (B and C) Mass of epiWAT (B) and BAT, including IsBAT and SubBAT (C) in wild-type (n = 6) mice and Apom À/À (n = 7) mice.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the present data should spark investigations to unravel a putative beneficial role of inhibiting the S1P 1 in, e.g., obesity and increased postprandial lipedema. Indeed, increased activity of BAT in humans has been associated with improved metabolic health from increased lipid metabolism, glucose uptake, and weight loss (Bartelt and Heeren, 2014;Cawthorne et al, 1984;Peirce and Vidal-Puig, 2013;Vallerand et al, 1986), and obese individuals also have reduced levels of BAT (van Marken Lichtenbelt et al, 2009). Inhibition of the apoM/S1P axis may provide a tool to address the extent to which stimulation of BAT is an effective means for improving metabolism in adult humans.…”
Section: Discussionmentioning
confidence: 99%